Simulasi Lintasan Partikel Bermuatan dalam Pengaruh Medan Listrik dan Medan Magnet Menggunakan Spreadsheet Excel - Sarman Sarman (SPEJ (Science and Physic Education Journal), 2022)
Abstract: This study aims to describe to students the physics phenomenon of the motion of charged particles in an electric and magnetic field and to simulate the trajectory of particles on a computer using an interactive spreadsheet. The spreadsheet is used to solve the analytical solution of the system of particle motion in the electromagnetic field. The results show that the graph plot of the numerical solution is immediately visible as a simulation of the trajectory of particles in an electromagnetic field. The simulation results show that the course of charged particles in an electromagnetic field depends on the strength of the electric field, magnetic field, particle mass, particle charge, initial velocity, and the angle between the electric field and magnetic field. Simulations developed using spreadsheets can be a powerful pedagogical tool in the study of physics. In conclusion, simulations using excel, as discussed above, appear to help students better understand the mathematical principles underlying physical phenomena and better appreciate the power of mathematics applied to the real world. The simulations generated in this study show that even without using macros, we can create sophisticated simulations. Keywords: Electromagnetic Field, Simulation, Spreadsheets